Exogenous HIV-1 Nef upsets the IFN-γ-induced impairment of human intestinal epithelial integrity. - Maria Giovanna Quaranta; Olimpia Vincentini; Cristina Felli; Francesca Spadaro; Marco Silano; Diego Moricoli; Luciana Giordani; Marina Viora (PLoS ONE, 2011)
The mucosal tissues play a central role in the transmission of HIV-1 infection as well as in the pathogenesis of AIDS. Despite several clinical studies reported intestinal dysfunction during HIV infection, the mechanisms underlying HIV-induced impairments of mucosal epithelial barrier are still unclear. It has been postulated that HIV-1 alters enterocytic function and HIV-1 proteins have been detected in several cell types of the intestinal mucosa. In the present study, we analyzed the effect of the accessory HIV-1 Nef protein on human epithelial cell line.We used unstimulated or IFN-γ-stimulated Caco-2 cells, as a model for homeostatic and inflamed gastrointestinal tracts, respectively. We investigated the effect of exogenous recombinant Nef on monolayer integrity analyzing its uptake, transepithelial electrical resistance, permeability to FITC-dextran and the expression of tight junction proteins. Moreover, we measured the induction of proinflammatory mediators. Exogenous Nef was taken up by Caco-2 cells, increased intestinal epithelial permeability and upset the IFN-γ-induced reduction of transepithelial resistance, interfering with tight junction protein expression. Moreover, Nef inhibited IFN-γ-induced apoptosis and up-regulated TNF-α, IL-6 and MIP-3α production by Caco-2 cells while down-regulated IL-10 production. The simultaneous exposure of Caco-2 cells to Nef and IFN-γ did not affect cytokine secretion respect to untreated cells. Finally, we found that Nef counteracted the IFN-γ induced arachidonic acid cascade.Our findings suggest that exogenous Nef, perturbing the IFN-γ-induced impairment of intestinal epithelial cells, could prolong cell survival, thus allowing for accumulation of viral particles. Our results may improve the understanding of AIDS pathogenesis, supporting the discovery of new therapeutic interventions.